Development of a Red Mud-Epoxy Intumescent Coating for Steel Structures - Mohd Asmadi, Mohd Amir (IRC, 2015)
The effect of red mud as filler in an intumescent coating with mixture of ammonium poly phosphate (APP), melamine (MEL), boric acid (BA), expandable graphite (EG), bisphenol A epoxy resin BE188 (BPA) and ACR hardener H-2319 was presented. Red mud is a waste product from Bayer process. It produces twice amount of red mud as waste compared to the alumina production. The amount of red mud was varied from 0 – 5 grams as to investigate the influence of red mud on the basic intumescent coating formulation on its fire retardant performance. The char expansion, residual weight of the intumescent coating and fire penetration test were executed. The coating went for furnace test at 500°C for 30 minutes as to analyze the char expansion and char structure. The optimum red mud amount as to get the largest char expansion was at 2 gram which is 3.69 times of the initial thickness. Fire test was conducted as to evaluate the heat penetration to the coated steel. The temperature of steel plate was recorded for 60 minutes at an interval of 1 minute. The results showed intumescent coating with red mud content protected steel at lower temperature compared to the constant formulation. With 2 gram of red mud, the coating successfully stabilized an impacting fire below 150°C for 60 minutes. The coating was characterized using thermal gravimetric analysis (TGA) at 10°C/min under N2, over the whole range of temperature between 50-800°C. The red mud increased the residual weight by 1.86% at 1g of red mud while decreased the residual weight for 11.05% at 3g of red mud and constant residual weight produced as to compare to the constant IC formulation when 5g of red mud was used. Therefore, red mud influenced the performance of the basic intumescent coating on its fire retardant properties. Utilization of red mud as filler reduced the environmental pollution as well as contributing to the safety of the society.